Mencari Bentuk Mengajar Entrepreneurship pada Perguruan Tinggi - Bambang Pratama (Bina Nusantara University, 2010)
The high number of unemployment in Indonesia is caused by college graduates not brave enough to determine a career path as an entrepreneur. The embedded bad image and false myths about entrepreneurs has made its spread very low in Indonesia. Universities in Indonesia are looking for a more effective form of teaching entrepreneurship so as to produce graduates who are productive rather than educated, but unemployed graduates. Entrepreneurship is very unique because it contains multiple disciplines. There are various forms of teaching entrepreneurship used by different countries in the world from various literatures. Universities and entrepreneur lecturers should be able to take an example on (adapt and adopt) how to teach according to the college culture and taught students, without having to look at what disciplines the student is enrolled in, also by integrating the values of entrepreneurship in the curriculum and extracurricular activities as supporting activities. Thus, entrepreneurial atmosphere can be created within the campus so that students, during their stay in college, do not seem to have lived and becoming used to a dynamic entrepreneurial environment, inspiring, and full of innovation. Thus, graduates will be braver in becoming an entrepreneur without it becomes their last choice like the current situation.